Design and Implementation of the Eleventwelfth Employee Attendance Website Using the Agile Method - Muhammad Nasir; Wicaksono, Aditya; Ramadhani, Kayla Attya; Saputra, Fikri; Darmansyah, Fadhlan Zaki; Septian, Muhammad Yordi (Journal of Informatics and Communication Technology (JICT), 2025)
This study aims to design and develop a web-based employee attendance system using the Agile methodology to improve the accuracy and efficiency of attendance records in the workplace. The system includes a location validation feature using Leaflet, an interactive mapping tool, to ensure that employees can only check in from approved locations. In addition, the system uses a webcam to capture a real-time photo of the employee during attendance as an extra layer of verification to prevent fraud. The development process includes requirements gathering, designing the user interface and database structure, building the application in stages, functional testing using the black-box method, and deploying the system in a real environment. The implementation results show that the system can accurately record real-time attendance, display user location on a map, and store attendance photos securely. This system supports a more transparent, secure, and accessible attendance management process. User feedback is collected for future improvements.